A Study on factors influencing farmers and dealers while selecting various brands of pesticides - SEEMA, P. LOKESH, MANOJ P. SAMUEL and (The Journal of Research, PJTSAU, 2017)
Agrochemicals occupy major share in the agribusiness wing of the agriculture sector. India is the 4th largest producer of agrochemicals globally with 125 technical grade manufactures, 800 formulators, over 145000 distributors (Federation of Indian Chambers of Commerce and Industry, 2013). Thus the Indian agrochemicals market is highly fragmented in nature and witnesses fierce competition with large number of organized sector players and significant share of spurious pesticides. In this scenario, every company wants to be dynamic in the race. This study will help the companies to understand the purchasing behaviour of the farmers and dealers in selecting pesticides amongst various brands.